Does Early Maternal Employment Harm Child Development? An Analysis of the Potential Benefits of Leave Taking - Baum II, Charles L. (Journal of Labor Economics, 2003)
More mothers engage in marketplace work today than ever before, with over 33% returning to work by the time their child is 3 months old. This article identifies the effects of maternal marketplace work in the initial months of an infant’s life on the child's cognitive development. Results suggest that such work in the first year of a child’s life has detrimental effects. Where significant, the results also indicate negative effects of maternal employment in the child’s first quarter of life. However, the negative effects of maternal marketplace work are partially offset by positive effects of increased family income.